Integrative Holistic Early Childhood Education (IH ECE) in Indonesia amidst the COVID 19 Pandemic - Heny Solekhah (International Journal of Emerging Issues in Early Childhood Education, 2022)
Integrative holistic services towards children in Indonesia has become a priority in Early Childhood Education (ECE). However, the COVID 19 pandemic had hindered its implementation, especially in how the teachers ought to accommodate the services of health and nutrition, parenting, and protection. The shifting school delivery from direct teaching to virtual classrooms was not anticipated. To maintain and increase the teachers’ competence in implementing integrative holistic services, around 60 teachers in Kendal Regency, Indonesia, had received six online workshops and seminars. The purpose of the research is to investigate the implementation of IH ECE by the teachers as well as to find its barriers during the pandemic. The descriptive qualitative research was employed by having three online focus groups discussions (FGD) with 17 teachers from 17 different subdistricts. The additional individual interviews, documents and literature were also conducted to strengthen the findings. The data reduction and triangulation were applied to the analysis. The research found that the teachers’ competence of ICT had improved on online teaching practices, by encouraging parents’ involvement at home. They attempted to apply STEAM learning was included in both online and limited face-to-face. For protection and health service, the teachers committed to implementing evidence-based first aid treatment for children. However, the parenting and nutrition services could not be optimum due to the physical distancing policy. It is suggested that the implementation of IH ECE amidst the pandemic requires more collaborations between the government institutions and society,